2022
DOI: 10.1038/s41398-022-01781-9
|View full text |Cite
|
Sign up to set email alerts
|

Social support mediates the influence of cerebellum functional connectivity strength on postpartum depression and postpartum depression with anxiety

Abstract: Post-Partum Depression (PPD) is the most common health issue impacting emotional well being in women and is often comorbid with anxiety (PPD-A). Previous studies have shown that adequate social support can protect against PPD and PPD-A. However, how the brain connectome is disrupted in PPD and PPD-A and the neural basis underlying the role of social support in PPD and PPD-A remains unclear. The present study aims to explore these issues in patients with PPD and PPD-A. Well-established questionnaires and restin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…PCL has bidirectional connections with precuneus ( 44 ), which is an important component of default mode network associated with mood disorder ( 45 ). Lots of research have shown structural and functional alterations in the PCL of depression and depression-related disorders ( 46 , 47 ). Therefore, combing the elevated HARS and HDRS scores in the patient group, the reduction of local functional connectivity in SMA and PCL may also be associated with the emotional disturbance in patients with TAO.…”
Section: Discussionmentioning
confidence: 99%
“…PCL has bidirectional connections with precuneus ( 44 ), which is an important component of default mode network associated with mood disorder ( 45 ). Lots of research have shown structural and functional alterations in the PCL of depression and depression-related disorders ( 46 , 47 ). Therefore, combing the elevated HARS and HDRS scores in the patient group, the reduction of local functional connectivity in SMA and PCL may also be associated with the emotional disturbance in patients with TAO.…”
Section: Discussionmentioning
confidence: 99%
“…Resting-state functional magnetic resonance imaging (rs-fMRI) has been used to detect spontaneous neural brain activity in PPD using the amplitude of low-frequency fluctuation (ALFF) analysis ( Deligiannidis et al, 2013 , 2019 ; Chase et al, 2014 ) or dynamic ALFF ( Cheng et al, 2022b ), regional homogeneity (ReHo) analysis ( Xiao-juan et al, 2011 ), voxel-mirrored homotopic connectivity ( Zhang et al, 2020 ), dynamic or static functional connectivity (FC) ( Cheng et al, 2022b ), functional connectivity density (FCD) ( Cheng et al, 2021 ), and functional connectivity strength (FCS) ( Cheng et al, 2022a ). Compared with healthy controls (HCs), mothers with PPD showed significantly increased ReHo in the posterior cingulate and medial frontal gyrus and decreased ReHo in the temporal gyrus ( Xiao-juan et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the altered FCD and resting-state FC were closely associated with depression and anxiety symptoms load ( Cheng et al, 2021 ). The PPD group showed specifically higher FCS in right parahippocampus, and perceived social support mediated the influence of FCS in the right cerebellum posterior lobe on depression and anxiety symptoms ( Cheng et al, 2022a ). These studies can help clarify how PPD may affect a mother’s baseline brain activity at rest and provide a more comprehensive understanding of neural circuitry dysfunction in mothers with PPD.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the contribution of each network during prediction, the identified networks through NMF method were classified into eight networks including seven cortical networks (visual network (VS), motor network (Dauvermann et al, 2021), limbic network (LMB, Cheng, Roberts, et al, 2022), default mode network (Dannlowski et al, 2012), ventral attention network (Cui et al, 2020), dordal attention network (Tomoda et al, 2009), frontoparietal network (FPN), and a cerebellum network in according to the Yeo group atlas (Yeo et al, 2011). Feature weights of each FNC were assigned to the corresponding connected networks, and the positive weights which made contribution for prediction were included.…”
Section: Methodsmentioning
confidence: 99%